The Role of Islam in the Formation of Civilization in Southeast Asia: History and Social Influence - Usman, Muhibuddin (Al-Fikrah, 2024)
Islam has played a significant role in the formation of civilization in Southeast Asia, particularly in terms of its historical and social influence. Since its arrival through trade routes and cultural exchanges, Islam has become an integral part of the region's identity. This article aims to explore how Islam contributed to shaping the social, political, and cultural structures of Southeast Asia. The study employs a historical-qualitative approach, focusing on historical literature and primary documents related to the development of Islam in the region. The findings indicate that Islam not only influenced social and cultural values but also played a critical role in shaping political identity and fostering relationships among diverse communities. The influence of Islam in Southeast Asia continues to this day, enriching social structures and strengthening cross-cultural ties.